(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A lake is the most beautiful and expressive feature of a landscape. It is often described as the “Eye of the Earth “. Urban lakes form vital ecosystems supporting livelihood with social, economic and aesthetic benefits that are essential for quality life. The nutrientpoor, oligotrophic lake is oxygen saturated and has a low microbial population whereas nutrient-rich, eutrophic lake has a bottom sediment layer and can have an anoxic hypolimnion. As microbial biomass increases with nutrient level, light penetration gets depleted. Thus the lower parts may receive poisonous gas like H2S released by anaerobes.